Pengaruh Kompensasi dan Motivasi terhadap Kinerja Pegawai di Kantor Kelurahan Langkai Kota Palangka Raya - Siren Siren; Andrea Oktaviani (Pencerah Publik, 2016)
This study aims to determine how much influence Compensation and Motivation has on Employee Performance in Langkai Village Office, and can find out which variables are most dominant in influencing Employee Performance. The type of research used is quantitative. The sample taken in the study saw a relatively small number of staff so that the entire population was used as samples called saturated samples. Where saturated samples are sampling techniques if all members of the population are used as samples. Data collection techniques with the questionnaire method. The questionnaire or questionnaire method according to Purwito is "an effort to collect information by delivering a number of written questions that are answered by the respondent". Based on the results of the research on the effect of compensation and motivation on employee performance in Langkai Kota Palangka Raya Village Office namely compensation has a negative effect on the performance of Langkai City Palangka Raya Urban Village Staff, Motivation has a positive effect on Langkai Kota Palangka Raya Village Staff Performance, and simultaneously, Compensation and Motivation have an effective positive towards the Performance of Langkai City Palangka Raya Urban Village Staff. But the most dominant Motivation variable affects Performance in Langkai City Palangka Raya Village Office.